Valuation of cow attributes by conjoint analysis: A case study of Western Kenya - Makokha, S.N.; Karugia, Joseph T.; Staal, Steven J.; Oluoch-Kosura,Willis (2007)
Better dairy production could reduce poverty and improve nutrition in western Kenya, but the requisite technologies have not been widely adopted. This study collected dairy cow attributes from 630 households to evaluate what factors influence smallholder farmers to adopt technologies. Conjoint analysis was used to compute the marginal rate of substitution between attributes, marginal willingness to pay, and marginal willingness to accept. Two ethnic groups had the highest willingness to pay for cattle with a high milk yield and low feed requirement. The highest marginal rate of substitution for cattle with a high disease resistance and a low feed requirement was from households with off-farm income, from areas with a good agro-climate, and from areas where cattle had cultural functions. The results suggest that farmers are more likely to choose cross-bred than high grade cows, and that extension services have little effect on their adoption of dairy technology. Kenya’s breed policy and infrastructure may need to be revised to reflect farmers’ needs.